The role of the court in debt restructuring - Payne, J (Cambridge University Press, 2018)
This paper examines the intervention of the law, and the role of the court, in debt restructuring, both in terms of imposing constraints on creditors and in seeking to ameliorate the potential abuses that can arise from such constraints. Three potential forms of abuse are examined: the imposition of a restructuring on dissenting creditors, which introduces the potential for wealth transfers between creditors; the imposition of a moratorium while a restructuring is negotiated, which might lead to misuse of the process by managers wishing to prop up companies which are not viable, or may allow managers of a viable business to ‘shake off’ liabilities that it is capable of servicing; and the facilitation of rescue finance, which raises the potential for new creditors to be preferred at the expense of existing creditors. It is argued that the court’s role in protecting creditors from these three forms of potential abuse is vital, although the nature of that role differs according to the form of abuse. Recent debt restructuring reform proposals in both the UK and the EU, which adopt quite different approaches to the role of the court in this process, are examined in the light of this discussion.